Splicing factor SRSF1 is essential for CD8 T cell function and host antigen-specific viral immunity - Juarez, Ignacio; Su, Shi; Herbert, Zachary T.; Teijaro, John R.; Moulton, Vaishali R. (Frontiers in Immunology, 2022)
Cytotoxic CD8 T cells are crucial for the host antigen-specific immune response to viral pathogens. Here we report the identification of an essential role for the serine/arginine-rich splicing factor (SRSF) 1 in CD8 T cell homeostasis and function. Specifically, SRSF1 is necessary for the maintenance of normal CD8 T lymphocyte numbers in the lymphoid compartment, and for the proliferative capacity and cytotoxic function of CD8 T cells. Furthermore, SRSF1 is required for antigen-specific IFN-γ cytokine responses in a viral infection challenge in mice. Transcriptomics analyses of Srsf1-deficient T cells reveal that SRSF1 controls cell cycle, MAP kinase signaling and IFN signaling pathways. Mechanistically, SRSF1 controls the expression and activity of the Mnk2/p38-MAPK axis at the molecular level. Our findings reveal previously unrecognized roles for SRSF1 in the physiology and function of cytotoxic CD8 T lymphocytes and a potential molecular mechanism in viral immunopathogenesis.